Malthusian pressures: Empirical evidence from a frontier economy - Vincent Geloso; Vadim Kufenko (Universität Hohenheim, 2015)
In this paper we study Malthusian pressures in a frontier economy. Using the empirical data on the real prices and demographic variables from 1688 to 1860 for Quebec and Montreal, we test for the existence of Malthusian pressures. Bearing in mind the particularities of frontier economies and the development of the Canadian economy, we conduct cointegration tests and VARs in order to identify positive and preventive checks. The cointegration test reveals absence of long-run equilibrium relationship between real wheat prices, birth and death rates. Using the Bai-Perron test we find a structural break in 1767 and divide the sample in pre- and post-conquest periods. We find that the positive checks were operating in the years prior to the conquest but that they faded during the nineteenth century. In the short-run, we find that wheat prices Granger-cause fluctuations in death rates in the pre-conquest period.
urn:nbn:de:bsz:100-opus-10567
Keywords: J11; N11; E32; 330; Malthusian economy; preventive check; positive check; Canadian history; empirical analysis